A Study on the Effect of Different Spacing Treatments on Yield from Eucalyptus tereticornis Plantations - Singh, S. P.; Lal, Purushottam; Muralidhar Rao, C. (Indian Forester, 1985)
The effect of different spacing treatments on yield from Eucalyptus plantations has been studied. It is observed that the spacing 1.0 m Ã— 1.0 m gives highest yield whereas spacing 2.5 m Ã— 2.5 m gives the lowest. The Spacing treatments do not seem to have any effect on survival of plants.